Study on natural dye extract from Melastoma malabathricum and nanostructured TiO2 as components in DYE-sensitized solar cells / Norkasmani Aziz - Norkasmani , Aziz (2019)
Dye-sensitized solar cells (DSSCs) or Graetzel cells are third generation solar cells. A huge variety of dyes including natural dyes can be used as sensitizers to provide the charge carriers. In the present work, anthocyanin that contains delphidin-3-glucoside and delphidin-3,5-glucoside has been extracted from the fruit pulp of Melastoma malabathricum. This study investigates the parameters that affect anthocyanin extraction from Melastoma malabathricum using the response surface method (RSM). Acidified methanol has been used for the anthocyanin extraction temperature between 30 and 80 °C. The fruit pulps of Melastoma malabathricum have been soaked between 60 to 180 min in trifluoroacetic acidified methanol content between 0.5 to 3%. These compounds are extracted for use in dye sensitized solar cells. Dye-sensitized solar cells were fabricated by sandwiching the polyacrylonitrile-based polymer electrolytes between TiO2/dye photoelectrode and platinum, Pt counter electrode, respectively. A simple technique was developed to fabricate a large-area TiO2 electrode layer using electrospun for dye-sensitized solar cells (DSSCs) via electrospinning technique. The electropsun TiO2 was further characterized in order to investigate the potential of these nanostructures to be used as component in DSSCs fabrications. The structures and properties of the electrospun solid and mesoporous TiO2 have been characterized by FESEM and XRD. For the first DSSC systems which contain commercial P25 TiO2, 5 wt.% of anthocyanin dyes (A3) exhibited the maximum efficiency of (1.054 ± 0.012)%. TiO2 nanoparticle/electrospun composite electrodes have been designed to increase the efficiency of dye adsorption in DSSCs application. 10 wt.% NRs and 90 wt.% of NPs (B1) resulted in improved efficiency up to (1.351± 0.013)%. The performance of NPs-NRs composite based DSSC was further improved by addition of sucrose and sucrose- DCA additives. For DSSC (NP-NRs) composite systems, the use of sucrose-DCA successfully improved the performances of DSSCs based Melastoma malabathricum anthocyanin. The performance was improved by addition of 6 wt.% sucrose-DCA compared to sucrose without DCA additive, in which the Jsc, Voc, FF, efficiency, Rs, Rsh and R2 values were (6.360 ± 0.059) mA cm-2, (0.473 ± 0.0.005) V, (0.656 ± 0.006), (1.974 ± 0.014) %, (0.013 ± 0.003) -cm2, (2.918 ± 0.019) -cm2 and (38.20 ± 0.17) , respectively.